PH-controlled synthesis of an aromatic triazene and its copper(II) complexation accompanied by an unexpected aromatic ring halogenation. (January 2017) - Xu, Dan; Geng, Jiao; Dai, Yuan; Peng, Yu-Xin; Qian, Hui-Fen; Huang, Wei
Abstract: An isomeric triazene (H2 L) and an azo dye (D1 ) were synthesized from the reaction between 2-amino-3-cyano-4-chloro-5-formylthiophene and 2-amino-5-nitrophenol under different pH values. Two Cu(II) complexes of the triazene H2 L formulated as {[Cu(L′)(H2 O)2 ]·DMF}n (C1 ) and [Cu2 L2 (DMF)2 ] (C2 ) were obtained by means of the reactions between deprotonated triazene ligand L 2− and different copper salts (CuCl2 ·2H2 O and Cu(OAc)2 ·H2 O) at room temperature. It is noted that a new in situ formed chlorinated ligand L′ 2- was obtained via the unusual Cu(II) mediated phenyl halogenation of L 2− evidenced by the formation of one-dimensional coordination polymerC1 in a high yield of 78%. A control experiment by using Cu(OAc)2 ·H2 O as the metal source reveals the formation of a dinuclear Cu(II) complexC2 of ligand L 2− without the occurrence of aromatic ring halogenation. It is suggested that the current study could present an effective approach to achieve the aromatic halogenation under a mild experimental condition with a high yield. Graphical abstract: Highlights: S -containing heterocyclic triazene and its isomeric azo dyes are described. Two heterocyclic triazene Cu(II) complexes have been firstly described. A new and facile approach on copper mediated aromatic halogenation is achieved. Representative crystal structures are obtained and compared.